Sudden Onset Proptosis: Frontal Sinus Mucocele Could Be a Cause - Jayshree Salam; Swati Kujur; Sushil Sachdeo; M. L. Garg (Delhi Journal of Ophthalmology)
Proptosis is one of the commonest clinical manifestations of orbital pathology. Apart from orbital pathology, paranasal sinus mucocele could be a cause of progressive, unilateral, and gradual onset of proptosis. Herein, we discuss a case of sudden onset of non axial unilateral proptosis with diminution of vision. CECT showed heterogeneous enhancing mass lesions causing expansion and destruction of roof of the left orbit and inferomedial displacement of eyeball. Endoscopic sinus surgery was done under general anaesthesia, followed by reduction in proptosis and normalization of eyeball position